Novel Approach for Endoscopic Management of Duodenal Injury during Perirenal Infected Haematoma Drainage after Shock-Wave Lithotripsy - Nariman Gadzhiev; Dmitry Gorelov; Alexander Smirnov; Salman Al-Shukri; Sergei Petrov (Case Reports in Urology)
Background. Gaining percutaneous access during percutaneous nephrolithotomy (PNL) can be complicated with the bowel injury. We report a novel approach of management of duodenal injury complicating percutaneous drainage of infected haematoma after Shock-Wave Lithotripsy (SWL). Case Presentation. A 57-year-old patient with the 15 mm right pelvic kidney stone underwent uneventful SWL. Patient visited emergency department 3 days later with high fever and chills with severe right flank pain. CT urography revealed lower pole kidney injury with signs of infected hematoma due to low attenuation areas but without signs of obstruction or urine leakage. Infected haematoma was drained percutaneously under ultrasound and X-ray control and a pigtail catheter 10 Fr was left beneath the lower pole of the right kidney. Postoperatively duodenal injury was suspected due to amber color, low creatinine, and high bilirubin level in the drainage output. CT demonstrated that the pigtail of the drain had entered the second part of the duodenum. Catheter was withdrawn and defect of the duodenal wall was stapled with four staples endoscopically. After 2 days of fasting patient was allowed to start oral food intake and was discharged on the 5th day. Conclusion. Injury of the duodenum during percutaneous kidney manipulation is an extremely rare complication. Conservative management consisting of endoscopic stapling of the duodenal wall defect is a safe and feasible approach to expediting the recovery of the patient.